PENGARUH E-COMMERCE TERHADAP PERILAKU KONSUMTIF MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS TANJUNGPURA PONTIANAK - Lam Alif Saputro; F. Y. Khosmas; M. Basri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine "The Effect of E-commerce on Consumptive Behavior in Economics Education Students, FKIP Untan Pontianak". The method used is a quantitative method with the form of relationship studies. The population is active students of the Pontianak Untan FKIP Economic Education class 2019, 2018 and 2017 regular A and the accelerated gross enrollment rate program (PPAPK) who have spent shopping through E-commerce. While the sample in this study amounted to 56 respondents obtained through simple random sampling technique. Data collection techniques using indirect communication techniques and documentary studies. The results of the study found that there was a significant positive effect of E-commerce on Consumptive Behavior in Economic Education Students of FKIP Untan Pontianak of 7.6% as evidenced by the Sig value of 0.040 <0.05 and in other words rejecting the null hypothesis (Ho) for variable testing , So the conclusion is that there is an effect of E-commerce on consumptive behavior in Economics Education Students FKIP Pontianak Untan amounting to 7.6%, while the remaining 92.4% is influenced by other factors not examined by researchersKeywords: E-commerce, Consumtive Behavior